The Burden of Adult X-Linked Hypophosphatemia on Carers and Family Members: A Mixed-Methods Study - Elina Matter; Claire Lawrence; Oliver Gardiner; Victoria Hayes; Gillian Logan; Ben Johnson; Andrew Lloyd (Journal of Health Economics and Outcomes Research)
# Introduction X-linked hypophosphatemia (XLH) is a rare, genetic disorder that severely impacts the health-related quality of life (HRQoL) of people living with the condition. This impact can also extend to carers and family members, described as a “spillover effect.” Measurement of spillover effects can lead to greater understanding of disease burden and potentially to more equitable decision-making regarding adoption of treatments by health technology assessment (HTA) bodies. This study aimed to explore spillover effects among carers and family members of adults with XLH.